The Analysis Of The Competence Of Business Administration Lecturers In Nasional Informatics Polytechnic - Salmah Harun (Fakultas Ekonomi Universitas Indonesia Timur, 2023)
The problem discussed in this study is the Competence of Business Administration Lecturers at the National Informatics Polytechnic. Based on these issues, this study aims to determine and analyze the Competencies of Business Administration Study Lecturers at the Makassar National Informatics Polytechnic. The research method used in this research is descriptive quantitative that describes the competence of Business Administration Study Program lecturers at the National Informatics Polytechnic. Analysis of the data used in this study is a quantitative descriptive analysis using a frequency distribution table by giving a percentage of each respondent's number of responses then analyzed and concluded using the Likert scale assessment category. The results showed that the pedagogical and professional competence of lecturers was already good. But it still needs to be improved, especially in terms of learning strategies. Lecturer Business Administration Program Competency at the National Informatics Polytechnic in terms of professional aspects is very good but lecturers still need to improve their knowledge. Lecturer Business Administration Program Competency at the National Informatics Polytechnic in terms of Personality is very good. Lecturer Business Administration Program Competency at the National Informatics Polytechnic in terms of social aspects is very good.